AKUNTANSI MANAJEMEN STRATEGIS DALAM PERSPEKTIF REVOLUSI INDUSTRI 5.0 - Indirman, Veri; Valdiansyah, Riyan Harbi; Rahayu, Sri (LPPM Universitas Bina Bangsa, 2024)
The Industrial Revolution has undergone several notable transformations, transitioning from the introduction of mechanization and steam power to the advent of digitalization, referred to as the Industrial Revolution 4.0. With the emergence of Industrial Revolution 5.0, or Society 5.0, emphasis has shifted towards the utilization of contemporary technologies, such as the Internet of Things (IoT), Artificial Intelligence (AI), and big data analysis, with the aim of effectively fulfilling human needs and enhancing social welfare. The overarching objective of Society 5.0 is to achieve harmonious equilibrium between economic progress and the resolution of social issues through the establishment of seamless interconnectivity between virtual and tangible realms. This study employed a qualitative methodology, specifically a scoping approach. It examines the impact of the Society 5.0 concept on the accounting perspective in strategic management, with the aim of facilitating more effective decision-making and enhancing the predictive capacity of an organization's future performance. The field of strategic management accounting, which supports the strategic management of corporations, has adapted to technological advancements. The application of digital technology in accounting enables more accurate and quality analyses, and improves the efficiency and effectiveness of the decision-making process. However, digital transformation also faces various challenges, including employee engagement, management support, and skill gaps. This research is expected to provide practical implications for industrial companies on how the Society 5.0 era changes the perspective of accounting in strategic management